Water management from an Islamic perspective - Saleem, Muhammad Yusuf (s.n, 2013)
Water is a basic and fundamental need for every living being whether they are human, animals or plants. Indeed, water is not only a basic need but a fundamental human right as there will be no life without water. Water related issues therefore should be the focus of our sustained research and investigation. In this research we discuss and investigate Quranic verses and Ahadith of the Prophet (PbAbuh) on the ownership of water resources, the right of the people to have a fair and equitable access to water resources and the management and privatization of water resources